2004
DOI: 10.1189/jlb.0504306
|View full text |Cite
|
Sign up to set email alerts
|

Impaired interleukin-8- and GROα-induced phosphorylation of extracellular signal-regulated kinase result in decreased migration of neutrophils from patients with myelodysplasia

Abstract: Patients with myelodysplasia suffer from recurrent bacterial infections as a result of differentiation defects of the myeloid lineage and a disturbed functioning of neutrophilic granulocytes. Important physiological activators of neutrophils are the cytokines interleukin-8/CXC chemokine ligand 8 (IL-8/CXCL8), which activates CXC chemokine receptor 1 and 2 (CXCR1 and CXCR2), and growth-related oncogene (GROalpha)/CXCL1, which stimulates only CXCR2. In this study, we show that migration toward IL-8/GROalpha grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 51 publications
4
38
0
Order By: Relevance
“…ERK inhibitors blocked CCL3-induced migration of GM-CSF-primed neutrophils in a study done by Ottonello and colleagues, 49 but Coffer and colleagues 48 found PI3-K dependence in GM-CSF-induced migration whereas inhibition of ERK with PD98059 had no effect. Fuhler and colleagues 47 showed that specific inhibitors for ERK1/2 abrogated neutrophil migration toward IL-8, similar to our own observation. However, in our experiments PI3-K/Akt, but not ERK activation was inhibited by prior heat.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…ERK inhibitors blocked CCL3-induced migration of GM-CSF-primed neutrophils in a study done by Ottonello and colleagues, 49 but Coffer and colleagues 48 found PI3-K dependence in GM-CSF-induced migration whereas inhibition of ERK with PD98059 had no effect. Fuhler and colleagues 47 showed that specific inhibitors for ERK1/2 abrogated neutrophil migration toward IL-8, similar to our own observation. However, in our experiments PI3-K/Akt, but not ERK activation was inhibited by prior heat.…”
Section: Discussionsupporting
confidence: 77%
“…Other investigators also reported the fact that PI3-K/Akt controls neutrophil migration in response to IL-8 or GM-CSF. 2,47,48 However, whether or not ERK is important for migration is still a matter of controversy. ERK inhibitors blocked CCL3-induced migration of GM-CSF-primed neutrophils in a study done by Ottonello and colleagues, 49 but Coffer and colleagues 48 found PI3-K dependence in GM-CSF-induced migration whereas inhibition of ERK with PD98059 had no effect.…”
Section: Discussionmentioning
confidence: 99%
“…31 We used the PathScan Intracellular Signaling Array Kit to monitor the expression of 18 signaling molecules that are phosphorylated in response to signal-transduction pathway activation. Treatment of both HUVECs and HDMECs with recombinant CXCL1 resulted in an increase in ERK1/2 signaling, and interference of CXCL1 function with neutralizing antibodies caused a corresponding decrease in phosphorylation of ERK1/2 (Figure 3a).…”
Section: Cxcl1 Stimulation Is Associated With Erk1/2 Signalingmentioning
confidence: 99%
“…Hcy also increases intracellular H2O2 production by neutrophils and neutrophil migration [2,3]. Hcy reduces endothelial nitric oxide synthase causing endothelial dysfunction [4,5].…”
Section: Introductionmentioning
confidence: 99%